A study of the recordkeeping practices of Victory Christian Fellowship (VCF) - Jimenez, Giselle M.
Just like organizations that conduct business and operations, churches also produce records that document their own operations. It is in this light that this study focused on the recordkeeping practices of Victory Christian Fellowship (VCF). Thirty local churches were surveyed as to how they manage their records according to the three stages of the Records Life Cycle. A focus group discussion (FGD) with Church Secretaries and interviews with the staff of Victory Ministers Association were likewise conducted to yield more accurate results on how the local churches manage their records.